Happiness and its relationship to the psychological immunity of a sample of orphan students in the upper basic stage in Jerash - Al- Ahmad, Mohammed Rafiq Mohammed (Journal of Educational and Psychological Sciences, 2020)
The present study aimed at identifying the level of happiness and its relationship with the psychological immunity of a sample of orphan students in the upper basic stage in Jerash governorate, and to achieve the objectives of the study were selected sample of students in the upper basic stage (grades eighth, ninth and tenth) reached (131) orphan students, The development of two measures, one for happiness and the other for psychological immunity, and the psychometric characteristics of them were verified. The results of the study found that the level of happiness and psychological immunity was average among orphan students, and there was a statistically significant correlation between most dimensions of happiness and psychological, as the results found that orphans students with a medium and high achievement level better in happiness than students with low achievement level, and based on the results of the study were some recommendations, including the need for attention by the counsellor some positive psychological variables among orphan students and work on programs counselling to them.